The answer is BAD. Hope this helps
Answer:
x = 4
Step-by-step explanation:
First you need to multiply both sides of the equation by -6/5
-6/5 × (-5/6x) = -6/5 × -10/3
Then you need to calculate and reduce. First, you'll reduce the numbers with the greatest common divisor, 6.
1/5 × 5x = -6/5 × (-10/3)
then reduce the greatest common divisor, 5
x = -6/5 × (-10/3)
Then multiply (multiplying two negatives equals a positive)
x = 6/5 × 10/3
reduce the greatest common divisor, 3
x = 2/5 × 10
reduce the greatest common divisor, 6
x = 2 × 2
x = 4
(i know this is confusing, sorry)
<span>z³ = 10,648
</span>z³ = 22³
z = 22
5 less (-5) than 1/3 of number (n/3) is (=) 2 more than (2+) half of the number (n/2)
-5+n/3=2+n/2
add 5 to both sides
n/3=n/2+7
times 6 both sides
2n=3n+42
minus 2n both sides
0=n+42
minus 42 boh sides
-42=n
the number is -42
the number is 18
2x^2 - y when x + 3 and y = -2
2(3)^2 - (-2)
2(9) + 4
18 + 4
22
Hope this helps,
Brian